Software in Metrology for the Digital Age: Addressing Compliance Challenges with MID, NAWID, and MDR - Koval Martin; Tesař Jiří; Staněk Martin; Foltýnek Jaroslav (EPJ Web of Conferences)
In the digital era, software is integral to devices regulated by European directives like MID, NAWID, and MDR, ensuring accuracy, reliability, and safety. While metrology has been crucial, software now plays an equally significant role, enabling data processing, automation, and new functionalities. Emerging technologies like AI, IoT, or cloud computing introduce compliance challenges. This article analyzes and compares software requirements in MID, NAWID, and MDR, focusing on software lifecycle, regulatory gaps, and risk assessment.